Integrated Management Model Based on Islamic Values to Improve The Quality of Islamic Educational Institutions in The Digital Era - Muhammad Idris; Dedi Irawan (CV. Edutechnium Indonesia, 2026)
This study aims to develop an integrated management model based on Islamic values as a solution for improving the quality of Islamic educational institutions in the digital era. The background of this research is the identification of various managerial problems in several madrasahs and Islamic boarding schools in the Pringsewu region, Lampung. These problems include weak strategic planning, lack of technology integration in management, and suboptimal data-based supervision. Initial observations at three institutions revealed that the existing management systems remained conventional and partial in nature. This study employed a mixed-method approach with a sequential explanatory design. Quantitative data were collected through questionnaires distributed to 85 respondents, consisting of teachers, staff, and institutional leaders. Qualitative data were obtained through in-depth interviews, participatory observation, and documentation studies. The results showed that the integrated management model, which combines Islamic values (honesty, trustworthiness, deliberation, and consistency) with digital systems (e-planning, e-organizing, e-actuating, e-controlling), significantly improved institutional quality. The average quality score increased from 2.65 to 4.32 on a 1-5 scale after six months of implementation. This finding offers novelty through an integrative approach that has not been widely developed in Islamic educational management in Indonesia. In conclusion, this model is recommended as a management standard for primary and secondary Islamic educational institutions.